Evaluation of Fontan liver disease: Correlation of transjugular liver biopsy with magnetic resonance and hemodynamics. (30th April 2019) - Silva‐Sepulveda, Jose A.; Fonseca, Yudy; Vodkin, Irine; Vaughn, Gabrielle; Newbury, Robert; Vavinskaya, Vera; Dwek, Jerry; Perry, James C.; Reshamwala, Preeti; Baehling, Cynthia; Lyon, James; Davis, Christopher; et al.
Abstract: Introduction: Liver fibrosis and cirrhosis are late complications in Fontan palliation. Liver biopsy is the gold standard. The goal of this study is to correlate transjugular liver biopsy (TJLB) in the setting of Fontan palliation with noninvasive testing and hemodynamics. Methods: Between August 2014 and July 2017, 49 Fontan patients underwent TJLB. All the patients had hemodynamic evaluation, 28 patients had MRE (magnetic resonance elastography) and 40 patients had cardiopulmonary exercise test. Histologic liver fibrosis was quantitated using traditional histologic scoring systems and a modified Ishak congestive hepatic fibrosis score. Results: Median age 17.8 years, median time since Fontan 15.2 years. Primary diagnosis and Fontan type were variables, but predominantly LV morphology (30/49), lateral tunnel Fontan (29/49), originally fenestrated (37/49), and 11/49 had a pacemaker. Histologic fibrosis correlated with MRE ( R = 0.62, P ≤ .001). Histologic fibrosis and MRE correlated with Fontan pressure ( R = 0.38, P = .008 & R = 0.59, P ≤ .001). Morphology of the single ventricle did not correlate with liver fibrosis. The presence of a fenestration resulted in a higher cardiac index ( P = .026) but did not resulted in lower liver fibrosis ( P = .64). Conclusion: Noninvasive tests, such as MRE, may be suitable for longitudinal follow‐up in patients with single ventricle physiology. Our data suggest that there is reasonable correlation of MRE liver stiffness with biopsy scoring systems and Fontan pressures. We demonstrated the feasibility of TJLB in the setting of Fontan palliation and demonstrated its correlation with noninvasive measures particularly MRE. We recommend selective use of TJLB when MRE score is >5 KPa or when there are other clinical signs of cirrhosis.